The effect of different concentrations of Neem (Azadiractha indica) leaves extract on the inhibition of Streptococcus mutans (In vitro) - Sri Kavi Subramaniam; Widowati Siswomihardjo; Siti Sunarintyas (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
The Neem plant has a history for treating gum and teeth problems and this plant is used for oral care in India. The active component (Azadirachta indica) has been proven to exhibit antibacterial properties. The objective of this study was to determine the influence of different concentrations of Neem leaves extract on the inhibition of Streptococcus mutans. Neem leaves extract at concentrations of 10%, 20%, 40%, 60%, 80%, and 100% was prepared. Fifty milliliters of each concentration were dropped into holes of 6 millimeters in diameter on a MHA agar that has been inoculated with Streptococcus mutans. Distilled water was used as a control. After 24 hours of incubation, the inhibition diameters were measured and analyzed. The statistical results of the one-way analysis of variance (ANOVA) illustrated that the different concentrations of Neem extract had a significant influence on the inhibition of Streptococcus mutans. This was followed with the Least Significant Difference (LSD) which implied that there were significant differences between all the concentrations of Neem leaves extract used in this experiment. The conclusion of this study was that Neem leaves extract exhibited antibacterial effect towards Streptococcus mutans and different concentration of Neem leaves extract influenced the inhibition of Streptococcus mutans.